(Pro)renin Receptor in Kidney Development and Disease. (30th May 2011) - Song, Renfang; Yosypiv, Ihor V.
Abstract : The renin-angiotensin system (RAS), a key regulator of the blood pressure and fluid/electrolyte homeostasis, also plays a critical role in kidney development. All the components of the RAS are expressed in the developing metanephros. Moreover, mutations in the genes encoding components of the RAS in mice or humans are associated with a broad spectrum of congenital anomalies of the kidney and urinary tract (CAKUT). These forms of CAKUT include renal papillary hypoplasia, hydronephrosis, duplicated collecting system, renal tubular dysgenesis, renal vascular abnormalities, and aberrant glomerulogenesis. Emerging evidence indicates that (pro)renin receptor (PRR), a novel component of the RAS, is essential for proper kidney development and that aberrant PRR signaling is causally linked to cardiovascular and renal disease. This paper describes the role of the RAS in kidney development and highlights emerging insights into the cellular and molecular mechanisms by which the PRR may regulate this critical morphogenetic process.